2020
DOI: 10.1021/acs.jchemed.0c00884
|View full text |Cite
|
Sign up to set email alerts
|

#DryLabs20: A New Global Collaborative Network to Consider and Address the Challenges of Laboratory Teaching with the Challenges of COVID-19

Abstract: Since the sudden emergence of COVID-19 global pandemic, all educational institutions have looked to move resources and delivery online. Some institutions had already embraced delivering instruction in this way, however, broader adaptation to this teaching style is new to many educators.While the teaching of theoretical concepts is more easily transferred to a blended learning environment, the teaching of practical chemistry poses significant challenges, yet it is crucial to the chemist's identity.Here we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…The results of our survey of MHSCI users and student outcomes suggest that students’ success is statistically similar with the shift to online lecture and lab compared with face-to-face and hybrid modalities prior to the COVID-19 pandemic. These results are consistent with previous pre-COVID-19 studies that showed no statistically significant differences in student success in fully online courses compared with face-to-face courses ( 9 11 ). However, further research and monitoring of student outcomes on the MHSCI will add greater depth to the insights gained from this brief analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our survey of MHSCI users and student outcomes suggest that students’ success is statistically similar with the shift to online lecture and lab compared with face-to-face and hybrid modalities prior to the COVID-19 pandemic. These results are consistent with previous pre-COVID-19 studies that showed no statistically significant differences in student success in fully online courses compared with face-to-face courses ( 9 11 ). However, further research and monitoring of student outcomes on the MHSCI will add greater depth to the insights gained from this brief analysis.…”
Section: Discussionsupporting
confidence: 92%
“…One study indicated that there was no difference in postgraduate degree programs among students in online upper-division life sciences courses compared with students in face-to-face modalities ( 10 ). With the advent of the COVID-19 pandemic and, for many institutions, the necessity of moving both lecture and lab course components to an online environment due to quarantine, concerns were expressed in the science education community about the impact on postsecondary science lecture and lab courses ( 11 ). Many science educators opted to shift to an entirely online modality for laboratory exercises ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the benefits of student engagement and hands‐on experiments it is very unfortunate that practical activities are currently facing several challenges. All over the world, there are less practical in‐person learning activities for undergraduate students because of one or more of these challenges; budget cuts (Baker & Verran, 2004; Hearing & Lu, 2014), increased use of technology (Jones, 2018), and the largest, most acute challenge; the ongoing COVID‐19 pandemic (Campbell et al., 2020; Sahu, 2020). During the COVID‐19 pandemic many universities all over the world were, and still are, faced with closed facilities (Bao, 2020; Sahu, 2020).…”
Section: Experiential Learning Off‐campusmentioning
confidence: 99%
“…During the COVID‐19 pandemic many universities all over the world were, and still are, faced with closed facilities (Bao, 2020; Sahu, 2020). Practical teaching had to be re‐designed to fit off‐campus teaching which had consequences for many important educational platforms in the STEM (Science, Technology, Engineering, and Mathematics) disciplines, such as laboratory training (Campbell et al., 2020; Noel et al., 2020), clinical laboratories (Cai et al., 2020; Franchi, 2020), and field courses (Barton, 2020; Creech & Shriner, 2020).…”
Section: Experiential Learning Off‐campusmentioning
confidence: 99%
“…As SARS-CoV-2 swept across the globe, educators were required to move teaching online at short notice, in what became known as emergency remote teaching [1]. While some elements of education were relatively straightforward to address, such as providing live online lectures or recordings to replicate face-to-face (F2F) sessions, others, particularly practical classes, have been far more problematic in the new blended learning model [2]. Over a year later, uncertainty remains over when students will be allowed back into the teaching laboratory.…”
mentioning
confidence: 99%